Business simulation games in developing pre-service restaurant managers’ speech interaction competence using GPTChat - Nikolaeva, Sofiya; Chernysh, Valentyna; Boyko, Anna; Galynska, Olena (My University, 2023)
The study aims to develop speech interaction skills in language learning of pre-service restaurant managers with focus on professional skills – decision-making in conflict and non-conflict communication situations using business simulation games; to explore the effectiveness of GPTChat as a tool for the development of students’ speech interaction competence in the context of business simulation games. A mixed research design was employed which involved 44 pre-service restaurant managers of the National University of Food technologies (Kyiv, Ukraine) in 2023. The quantitative research method was used to assess the students’ level of speech interaction competence using the Fisher Criterion. The qualitative research method was used for analyzing and interpreting data of the experimental learning. The results showed that the pre-service restaurant managers who were consulted by teachers, used GPTChat and business simulation games for developing their speech interaction and decision-making skills had higher results than those who only used GPTChat. It has been found that business simulation games allow pre-service restaurant managers to better understand the nature of conflict and non-conflict situations in their professional field, develop speech interaction competence, practice in decision-making in simulation environment. GPTChat can be used as a tool for creating various professional situations, analysing the algorithms of decision-making in conflict and non-conflict situations. Дослідження спрямоване на формування мовленнєвої компетентності майбутніх менеджерів ресторанного господарства з акцентом на професійні навички – прийняття рішень у конфліктних та неконфліктних ситуаціях з використанням ділових ігор, дослідження ефективності використання GPT чату як інструменту для формування мовленнєвої компетентності студентів у контексті ділових ігор. Було застосовано змішані методи дослідження,у якому взяли участь 4 майбутніх менеджера ресторанного господарства,які навчаються у Національному університеті харчових технологій (Київ, Україна). Дослідження проводилось у першому семестрі 2022-2023 навчального року. За допомогою кількісного методу дослідження було визначено рівень сформованості мовленнєвої компетентності студентів за допомогою критерію Фішера. Для аналізу та інтерпретації даних експериментального навчання використовувався якісний метод дослідження. Результати показали, що майбутні менеджери ресторанного господарства, які консультувались з викладачами, використовували GPT чату та ділові ігри для розвитку своєї мовленнєвої компетентності, мали вищі результати,ніж ті студенти, які використовували лише GPT чат. Встановлено, що ділові ігри дозволяють майбутнім менеджерам ресторанного господарства краще зрозуміти природу конфліктних і неконфліктних ситуацій у своїй професійній сфері, розвивати мовленнєву компетентність з допомогою ділових ігор. GPT чат можна використовувати як інструмент для створення різноманітних професійних ситуацій, аналізу алгоритмів прийняття рішень у конфліктних і неконфліктних ситуаціях.
Keywords: кафедра іноземних мов професійного спрямування; business simulation game; pre-service restaurant managers; speech interaction competence; GPTChat; conflict / non-conflict communication situations; decision-making; ESP; ділова гра; майбутні менеджери ресторанного господарства; мовленнєва компетентність; GPT чат; конфліктні/неконфліктні комунікативні ситуації; прийняття рішень; іноземна мова професійного спрямування